El sueño de la nación produce ensayos: el ensayismo de reflexión nacional de Joan Fuster - Roberto Rodríguez Milán (Cahiers de Civilisation Espagnole Contemporaine)
The article studies the intellectual origins of the Spanish writer Joan Fuster i Ortells (1922-1992) and the main characteristics of his abundant written production related to «reflecting upon the nation» –this is the essays Joan Fuster dedicates to the history and culture of Catalonia, its present, its future and its conflicts with the Spanish cultural nationalism.